Assessing Model of Financial Satisfaction Predictors: the Mediating Effect of Financial Risk Tolerance and Financial Behavior - Yuliani, Yuliani; Taufik, Taufik; Mukhtaruddin, Mukhtaruddin; Dewi Murnila Saputri, Nyimas (Journal of Accounting Research, Organization and Economics, 2021)
Objective This study aims to prove empirically about the prediction of financial satisfaction models based on financial knowledge and socio-economic factors of finance by taking into account financial risk tolerance and financial behavior.Design/methodology The primary data source in the form of a questionnaire and non-probability purposive sampling technique were used with 107 responses collected during July-August 2020. The unit of analysis was an individual, namely the people in Palembang City in the age range of 20-55 years. Data analysis comprise of descriptive statistics index number method and inferential statistics SEM method by converting ordinal data into intervals.Results It was found that direct financial knowledge, socio-economic financial had not significant on financial risk tolerance. Financial knowledge, socio economic financial significantly and positively influence financial behavior. Furthermore, direct financial knowledge, socio-economic financial, financial risk tolerance, financial behavior had a significant positive effect on financial satisfaction. The indirect effect found that finance risk tolerance is not a mediation of the influence of financial knowledge and socio-economic financial on financial satisfaction. The indirect effect of financial behavior on the influence of financial knowledge and financial socio-economic were significant.Limitation/Suggestion This study implies that the role of financial behavior as a partial mediation on the relationship between financial knowledge and financial satisfaction. The role of perfect mediation itself is for socio-economic financial relationships and financial satisfaction.